University Campus Living Labs. Unpacking Multiple Dimensions of an Emerging Phenomenon - Nyborg, Sophie; Horst, Maja; O’Donovan, Cian; Bombaerts, Gunter; Hansen, Meiken; Takahashi , Makoto; Viscusi, Gianluigi; Ryszawska, Bozena (Science & Technology Studies, 2024)
Universities and their changing role in society is a source of perennial debate. In this article, we examine the emergent phenomenon of University Campus Living Labs (UCLL), the set of practices by which universities use their own buildings, streets or energy infrastructure as experimental settings in order to support applied teaching, research and co-creation with society. While most existing studies of UCLLs focus on them as sustainability instruments, we explore the UCLL phenomenon from an open-ended and fresh angle. Using living labs in five European universities as exemplary cases, we demonstrate the breadth and variability of this emerging phenomenon through five analytical dimensions to unpack the multiple forms and purposes that UCLLs can have. We furthermore consider aspects of inclusiveness and situatedness of living lab co-creation and testing and what the UCLL phenomena may come to mean for the continuously changing university, calling for future studies to substantiate these aspects.